Pneumolysin as a target for new therapies against pneumococcal infections: A systematic review. - María Dolores Cima Cabal; Felipe Molina; José Ignacio López-Sánchez; Efrén Pérez-Santín; María Del Mar García-Suárez (PLoS ONE, 2023)
Background This systematic review evaluates pneumolysin (PLY) as a target for new treatments against pneumococcal infections. Pneumolysin is one of the main virulence factors produced by all types of pneumococci. This toxin (53 kDa) is a highly conserved protein that binds to cholesterol in eukaryotic cells, forming pores that lead to cell destruction. Methods The databases consulted were MEDLINE, Web of Science, and Scopus. Articles were independently screened by title, abstract, and full text by two researchers, and using consensus to resolve any disagreements that occurred. Articles in other languages different from English, patents, cases report, notes, chapter books and reviews were excluded. Searches were restricted to the years 2000 to 2021. Methodological quality was evaluated using OHAT framework. Results Forty-one articles describing the effects of different molecules that inhibit PLY were reviewed. Briefly, the inhibitory molecules found were classified into three main groups: those exerting a direct effect by binding and/or blocking PLY, those acting indirectly by preventing its effects on host cells, and those whose mechanisms are unknown. Although many molecules are proposed as toxin blockers, only some of them, such as antibiotics, peptides, sterols, and statins, have the probability of being implemented as clinical treatment. In contrast, for other molecules, there are limited studies that demonstrate efficacy in animal models with sufficient reliability. Discussion Most of the studies reviewed has a good level of confidence. However, one of the limitations of this systematic review is the lack of homogeneity of the studies, what prevented to carry out a statistical comparison of the results or meta-analysis. Conclusion A panel of molecules blocking PLY activity are associated with the improvement of the inflammatory process triggered by the pneumococcal infection. Some molecules have already been used in humans for other purposes, so they could be safe for use in patients with pneumococcal infections. These patients might benefit from a second line treatment during the initial stages of the infection preventing acute respiratory distress syndrome and invasive pneumococcal diseases. Additional research using the presented set of compounds might further improve the clinical management of these patients.